An Estimation of the Grant Element in Foreign Aid (The Pakistan Development Review, 1977)
The purpose of aid is to effect a real transfer of resources from the developed countries to the developing ones. Aid can be given through a number of arrangements which differ from one donor country to another. The three main variables that influence the terms of aid are the interest rate, the grace period and the repayment period. Another factor that may influence these terms is the possibility that the loan may be repayable in local instead of convertible currency; if this is so, then the grant element of the loan increases.1 However, this possibility is ignored when calculating the grant element in this paper as it occurs infrequently in repayment agreements.